2022
DOI: 10.1093/eurheartj/ehac015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of statin intolerance: a meta-analysis

Abstract: Aims Statin intolerance (SI) represents a significant public health problem for which precise estimates of prevalence are needed. Statin intolerance remains an important clinical challenge, and it is associated with an increased risk of cardiovascular events. This meta-analysis estimates the overall prevalence of SI, the prevalence according to different diagnostic criteria and in different disease settings, and identifies possible risk factors/conditions that might increase the risk of SI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
4
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(175 citation statements)
references
References 210 publications
5
157
4
9
Order By: Relevance
“… 15 A recent meta‐analysis by the Lipid and Blood Pressure Meta‐analysis collaboration (LBPMC) Group, and the International Lipid Expert Panel (ILEP) has demonstrated that intolerance occurs worldwide in between 5.9 and 7.0% (depending on the diagnostic criteria used) of statin‐treated patients worldwide. 16 It is therefore imperative that practitioners have clear guidance about how to manage muscle symptoms in individuals on statin therapy. The clear aim of the guidance should be to enable patient‐centred discussions about the benefits and risks of treatment to ensure that lipid‐lowering therapy (LLT) is not stopped inappropriately and that effective CV risk‐reduction strategies are made available for individuals who cannot tolerate statin therapy at the necessary intensity to ameliorate their CVD risk.…”
Section: Introductionmentioning
confidence: 99%
“… 15 A recent meta‐analysis by the Lipid and Blood Pressure Meta‐analysis collaboration (LBPMC) Group, and the International Lipid Expert Panel (ILEP) has demonstrated that intolerance occurs worldwide in between 5.9 and 7.0% (depending on the diagnostic criteria used) of statin‐treated patients worldwide. 16 It is therefore imperative that practitioners have clear guidance about how to manage muscle symptoms in individuals on statin therapy. The clear aim of the guidance should be to enable patient‐centred discussions about the benefits and risks of treatment to ensure that lipid‐lowering therapy (LLT) is not stopped inappropriately and that effective CV risk‐reduction strategies are made available for individuals who cannot tolerate statin therapy at the necessary intensity to ameliorate their CVD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, many patients struggle with statin-associated muscle symptoms. In a recent meta-analysis including more than 4 million patients, the overall prevalence of statin intolerance was 9.1% and might often be overestimated ( 18 ). N-of-1 trials such as the SAMSON study demonstrated that also in patients with a history of statin intolerance, effective statin therapy could be established in approximately 50% of patients with prior symptoms ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the most recent data, the worldwide prevalence of statin intolerance is 9.1% [59][60][61][62][63][64]. Patients who report symptoms of statin intolerance should always be diagnosed based on the approved definitions [9] assessed using the statin associated muscle symptoms clinical index (SAMS-CI) [65].…”
Section: Lipid-lowering Therapymentioning
confidence: 99%